ANALISIS PEMILIHAN BANK SYARIAH DENGAN PENDEKATAN ANALYTICAL HIERARCHY PROCESS - NURUL KHOTIMAH, HENIFFA Nurul (Jurnal Akuntansi AKUNESA, 2013)
Analytical Hierarchy Process (AHP) is a method of decision making to thechoice priority determining problem of many alternatives. Based on the identification offactors that affect of decision making process of bank selection developed three levels.The first level is the goal of the problems of the bank selection. The second level is afactor taken into consideration in the selection of banks, consisting of five factors, theminimum initial deposit, satisfaction of service facilities, the number of branch offices,administrative costs and CAR (Capital Adequacy Ratio). The third level is the bankalternatives. In this research, the alternative bank is Bank Syariah Mandiri and BankBRI Syariah.Keyword: AHP, Analytical Factors,Bank Selection.